Revitalisation of women's skills in the public sector : a view into the 4th Industrial Revolution - Kanjere, M. M. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
The 4th Industrial Revolution has challenged organisations and governments to relook into their skills and to adjust accordingly. Various industrialisations have had a different impact on both men and women, with most women playing a catch up game. This is because most women were ill equipped to deal with the developments. In most instances, developments and adjustments are likely to attract men who are well positions to lead. When growth opportunities are presented, men are given preference over women. Thus, this paper aims at probing the extent to which the South African government has developed strategies of revitalising the skills of women in the public sector to navigate the 4th Industrial Revolution challenges. The paper also argues that the previous contributions of women in various fields of industrialisations have been unrecognised in the chronicles of human accomplishments. This is because the written histories of industrialisation over the years have overlooked the women's contribution as insignificant, even though some of their work was distinctive. Thus, a desktop analysis was used to investigate the problem. The findings of the investigation highlighted lack of concise strategy that is used to develop the technological skills of women in the public sector. Therefore, this paper proposes a framework that can be considered as one of the strategies of revitalising the skills of women in the public sector.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Industrialisations; Revitalisation; Skills; Strategies; Job enrichment; Career development; Women in the professions